2023
DOI: 10.1161/atvbaha.122.318062
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A1 Protects Against Necrotic Core Development in Atherosclerotic Plaques: PDZK1-Dependent High-Density Lipoprotein Suppression of Necroptosis in Macrophages

Abstract: BACKGROUND: Atherosclerosis is a chronic disease affecting artery wall and a major contributor to cardiovascular diseases. Large necrotic cores increase risk of plaque rupture leading to thrombus formation. Necrotic cores are rich in debris from dead macrophages. Programmed necrosis (necroptosis) contributes to necrotic core formation. HDL (high-density lipoprotein) exerts direct atheroprotective effects on different cells within atherosclerotic plaques. Some of these depend on the SR-B1 (scavenger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 122 publications
1
3
0
Order By: Relevance
“… 29 ApoA1 in vivo prevents necrotic prolapse and necrotic core formation in macrophages in atherosclerosis. 10 In our study, Correlation analysis and multiple linear regression showed that plasma ketones levels were negatively correlated with apoA1. Du et al suggested that TG, TC, and LDL-C were higher in young KPT2D than in T2D.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“… 29 ApoA1 in vivo prevents necrotic prolapse and necrotic core formation in macrophages in atherosclerosis. 10 In our study, Correlation analysis and multiple linear regression showed that plasma ketones levels were negatively correlated with apoA1. Du et al suggested that TG, TC, and LDL-C were higher in young KPT2D than in T2D.…”
Section: Discussionsupporting
confidence: 54%
“… 9 HDL has a direct atheroprotective effect on different cells within the atherosclerotic plaque. 10 The body can excrete cholesterol and other lipids by reverse transportation of cholesterol, thus preventing atherosclerosis. ApoA1 is an important component of HDL and plays a key role in the reverse cholesterol transport.…”
Section: Introductionmentioning
confidence: 99%
“…38 In addition, the ability of ApoA1 to restrain necroptosis in macrophages and inhibit the formation and development of necrotic cores in atherosclerosis may contribute to those mechanisms. 39…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that the HDL treatment of both THP-1 and murine peritoneal macrophages suppressed necroptosis induced by TNF or oxLDL in the presence of the pan-caspases inhibitor. This protective effect was contingent on the HDL receptor SR-B1 and activation of Akt kinase ( 181 ).…”
Section: Cell Death In Atherosclerotic Plaques: Pyroptosis Necroptosi...mentioning
confidence: 99%